Flora apícola para Apis mellifera L. (Hymenoptera: Apidae) em municípios sergipanos - Rolim, Gabriela da Silva (2015)
The recognition of the regional beekeeping flora is a form of information on the dynamics of the trophic niche of Apis mellifera, allowing the use of coherent way of the features offered by native flora as well as assist in the management operations of an apiary and valuation of bee products. The objective was to characterize the bee flora in honey and pollen samples in apiaries producers in four municipalities belonging to the region of east of Sergipe (Neópolis, Japaratuba, São Cristovão e Estância). Exsiccates were prepared for identification of botanical species. Samples of honey, bee pollen in three colonies were collected from Apis mellifera, and plants surrounding the apiary at 12 months. The identification of the botanical species was performed by comparison with the aid of the reference blades prepared from flower buds of blooming species situated approximately the apiary. The samples of honey, bee pollen and flower buds were sent to the Forest Entomology Laboratory / UFS, being submitted to acetolysis analysis and blades made with glycerin jelly for qualitative and quantitative evaluation of pollen in honey and bee pollen. Approximately the apiaries were identified an average of 43 botanical species by city, and the plants of Asteraceae and Fabaceae families the most representative, with seven to ten species respectively. In samples of pollen, the Fabaceae family presented greater number of species, and the pollen grains of species Mimosa pudica and Mimosa caesalpiniaefolia frequently in the municipalities of Neópolis, Japaratuba and São Cristóvão, and the Estância municipality of the most frequent species was Cocus nucifera Arecaceae family. In addition, encountered during 10 the 12 months evaluated. Fabaceae was also the most representative family in honey samples analyzed, with the species Chamaecrista flexuosa, M. caesalpiniaefolia, M. pudica and M. tenuiflora, being found in the four cities studied. Arecacea and Fabaceae were the most important families, frequent and abundant for samples of honey and pollen can be considered essential for pollen production in the study area. The Sergipe beekeepers in the possession of this information can maximize production and add value to the final product, by botanical certification of their products.